Daptomycin Pharmacokinetics in Blood and Wound Fluid in Critical Ill Patients with Left Ventricle Assist Devices - Stefanie Calov; Frederik Munzel; Anka C. Roehr; Otto Frey; Lina Maria Serna Higuita; Petra Wied; Peter Rosenberger; Helene A. Haeberle; Kristian-Christos Ngamsri (MDPI AG, 2023)
Daptomycin is a cyclic lipopeptide antibiotic with bactericidal effects against multidrug-resistant Gram-positive bacteria, including methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant Enterococcus faecalis (VRE). For critically ill patients, especially in the presence of implants, daptomycin is an important therapeutic option. Left ventricle assist devices (LVADs) can be utilized for intensive care patients with end-stage heart failure as a bridge to transplant. We conducted a single-center prospective trial with critically ill adults with LVAD who received prophylactic anti-infective therapy with daptomycin. Our study aimed to evaluate the pharmacokinetics of daptomycin in the blood serum and wound fluids after LVAD implantation. Daptomycin concentration were assessed over three days using high-performance liquid chromatography (HPLC). We detected a high correlation between blood serum and wound fluid daptomycin concentration at 12 h (IC95%: 0.64 to 0.95; r = 0.86; p < 0.001) and 24 h (IC95%: −0.38 to 0.92; r = 0.76; p < 0.001) after antibiotic administration. Our pilot clinical study provides new insights into the pharmacokinetics of daptomycin from the blood into wound fluids of critically ill patients with LVADs.